The Effect Of Entrepreneurial Orientation, Innovation Capability, Market Orientation, And Networking Capability On Business Sustainability Of SMES - Acep Fatchuroji; Candra Agus Wahyudhi; Mutiya Oktariani; Damayanti; Rawuh Yuda Yuwana; Juli Arianti (Economics and Business Journal (ECBIS), 2026)
The current study addresses the impact of entrepreneurial orientation, innovation capability, market orientation, and networking capability on business sustainability in small and medium enterprises (SMEs). The contribution of SMEs to economic development is important; however, sustainability in these entities can be threatened by resource scarcity and rapidly changing environments in markets. The current study adopts a quantitative approach that entails data collection using a structured questionnaire targeting owners and managers in SMEs. The collected data were analyzed through statistical methods to analyze the relationship among study variables. The results of this study indicate that entrepreneurial orientation, innovation capability, market orientation, and networking capability are positive and influential factors in improving business sustainability in SMEs. Market orientation and innovation capability have higher influences on sustainability in SMEs than other factors since customer-centric approaches and innovation have playing crucial roles in ensuring sustainability in business operations for these entities. This study is an important addition to existing theories since this research adopts an integrated approach within strategic capabilities for improved adaptability and sustainability of SMEs in competitive markets